Pendampingan Berhitung Pada Anak Sekolah Dasar Menggunakan Media “Papan Pintar Berhitung” - Siti Dian Mulyanti; Siti Nurhasanah; Dede Imtihanudin; Badri Munawar; Linda Linda (Institut Nalanda, 2023)
The purpose of this mentoring activity is to teach the concept of counting to elementary school media. This training activity consisted of 3 stages, namely the first stage of observation, the second stage students in the base village of the base village by using the